2022
DOI: 10.3390/beverages8040083
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Three Post-Harvest Methods at Different Altitudes on the Organoleptic Quality of C. canephora Coffee

Abstract: C. canephora (syn. C. robusta) is distinctive due to its rising industrial value and pathogen resistance. Both altitude and post-harvest methods influence coffee cup quality; however, modest information is known about this coffee species. Therefore, the aim of this study was to determine the relationship between four different altitudes and post-harvest processes (dry, honey, and wet) to the improvement of the organoleptic quality of the C. canephora congolensis and conilon drink. For dry processing, congolens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…Environmental conditions such as growing altitude and shade impact the sensory quality of coffee. Previous research reported a positive impact of higher altitude on the sensory quality of Robusta (Velásquez et al, 2022) and Arabica cultivars (Avelino et al, 2005;Tolessa et al, 2017;Worku et al, 2018;Koutouleas et al, 2023). Previous studies also reported both a positive effect (Vaast et al, 2006;Worku et al, 2018) and a negative effect (Bosselmann et al, 2009;Tolessa et al, 2017) of shade on the sensory quality of Arabica coffee.…”
Section: Discussionmentioning
confidence: 92%
“…Environmental conditions such as growing altitude and shade impact the sensory quality of coffee. Previous research reported a positive impact of higher altitude on the sensory quality of Robusta (Velásquez et al, 2022) and Arabica cultivars (Avelino et al, 2005;Tolessa et al, 2017;Worku et al, 2018;Koutouleas et al, 2023). Previous studies also reported both a positive effect (Vaast et al, 2006;Worku et al, 2018) and a negative effect (Bosselmann et al, 2009;Tolessa et al, 2017) of shade on the sensory quality of Arabica coffee.…”
Section: Discussionmentioning
confidence: 92%
“…This stage is vital because the outcome of post-harvest processing directly influences the harvest's added value or market value. Post-harvest processing is also crucial for enhancing the quality of coffee [15][16][17][18][19][20]. Postharvest processing is crucial due to the market demand for specialty coffee.…”
Section: Introductionmentioning
confidence: 99%